2008
DOI: 10.1086/589981
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of an Industrial Systems-Engineering Approach to Reduce the Incidence of Methicillin-ResistantStaphylococcus aureusInfection

Abstract: Sustained reduction in the incidence of MRSA infection is possible in a setting where this pathogen is endemic. An industrial systems-engineering approach can be adapted to facilitate consistent and reliable adherence to MRSA infection prevention practices in healthcare facilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 31 publications
2
25
1
1
Order By: Relevance
“…The Veterans Health Administration (VHA) was an early adopter of active universal nasal MRSA colonization surveillance for all patients admitted to acute-care facilities, with many hospitals and states subsequently following this course (8,13).…”
mentioning
confidence: 99%
“…The Veterans Health Administration (VHA) was an early adopter of active universal nasal MRSA colonization surveillance for all patients admitted to acute-care facilities, with many hospitals and states subsequently following this course (8,13).…”
mentioning
confidence: 99%
“…6 The manufacturing quality tools such as Lean management (LM) and Six Sigma (SS) are being implemented more frequently at hospitals around the world in an effort to raise patient and personnel satisfaction as well as improving healthcare quality on different settings, increasing efficiency and saving unnecessary costs. [7][8][9][10][11] In a systematic review of the literature, 177 articles on productivity tools used in health care have been published during the last decade. 12,13 These reports have shown that the implementation of process improvement tools positively impact OR efficiency without impairing the quality of patient care.…”
Section: Discussionmentioning
confidence: 99%
“…Keywords assessment, benchmark, comparison, measurement, quality but increasingly this is occurring [5,6,7 ]. These tools supplement traditional medical quality assurance tools such as continuing education, case reports, clinical trials, journal clubs and professional responsibility.…”
Section: Recent Findingsmentioning
confidence: 99%